Graphitization method of lithium ion battery negative electrode material and lithium ion battery negative electrode material
By pretreating the negative electrode powder and burning the graphitization barely in the Atchison graphitization furnace, the problem of high energy consumption in the graphitization process of lithium-ion battery negative electrode materials is solved, the production of high-performance materials is realized and the cost is reduced .
Patent Information
- Application Number
- CN202310694855.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-13
- Publication Date
- 2024-12-20
AI Technical Summary
The energy consumption in the graphitization process of the negative electrode materials of existing lithium-ion batteries affects the quality of materials and production costs.
By pretreating the negative electrode powder, adding binder and auxiliary additives to make blocks, and barely burned graphitization in an Atchson graphitization furnace, reducing energy consumption and saving crucible costs.
It significantly reduces the energy consumption during graphitization, and at the same time improves the specific surface area, graphitization degree and first effect of the negative electrode material of lithium-ion battery, saving crucible cost.
Smart Images

Figure CN119160886A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of negative electrode materials for lithium ion batteries and relates to a graphitization method for negative electrode materials for lithium ion batteries, which can greatly reduce the energy consumption during the graphitization process of the negative electrode materials. Background Art
[0002] With the rapid development of the global new energy industry, new energy vehicles, energy storage equipment and consumer electronics have all seen unprecedented strong demand, and the demand for graphite negative electrode materials has also increased significantly. As a key material for lithium-ion batteries, graphite negative electrode materials have gradually become the mainstream of the negative electrode material market, accounting for about 70% of the market share. The graphitization process of artificial graphite negative electrode materials is a key point that affects the quality of negative electrode materials and is also a technical difficulty.
[0003] The processing of negative electrode materials is mainly divided into two key links: granulation and graphitization, and both have high technical barriers; negative electrode materials can significantly improve the specific capacity, first effect, specific surface area, compaction density, conductivity, chemical stability and other performance indicators of negative electrode materials through graphitization, so controlling and mastering the graphitization process technology is an important way to ensure the quality of negative electrode materials. The graphitization process is to make full use of resistance heat to heat the carbonaceous material to 2300-3000℃, so that the amorphous chaotic layer structure of carbon is transformed into an ordered graphite crystalline structure. The energy for the transformation of graphite crystalline structure and atomic rearrangement comes from high-temperature heat treatment. With the increase of heat treatment temperature, the spacing between graphite layers gradually decreases, generally between 0.343 and 0.346nm. Generally, the temperature changes significantly at 2500℃, and the change gradually slows down at 3000℃ until the entire graphitization process is completed. Artificial graphite negative electrode materials are successfully transformed into graphite structures through high-temperature graphitization treatment, and have the corresponding functions of lithium battery negative electrodes.
[0004] There are four main types of furnaces used in the graphitization process of negative electrode materials: Acheson graphitization furnace, internal string graphitization furnace, box-type graphitization furnace and continuous graphitization furnace. Their advantages and disadvantages, as well as the performance of the prepared products are shown in Tables 1 and 2.
[0005] Table 1 Comparison of advantages and disadvantages of different graphitization furnace types
[0006] Table1 Comparison of diffenent graphitization fumaces
[0007]
[0008] Table 2 Process unit consumption and product performance of different graphitization furnaces
[0009] Table2 Process unit consumption and product perfrmance different graphiyization fumaces
[0010]
[0011] Among the above four types of furnaces, the most commonly used is the Acheson graphitization furnace, and a small amount of the inner string graphitization furnace is used. Box-type graphitization furnace and continuous graphitization furnace are new furnace types developed in recent years. The box-type graphitization furnace has developed rapidly, mainly through the transformation of the Acheson furnace and some new construction. Since the box-type graphitization furnace and the continuous graphitization furnace are newly built and are still in the trial process, their furnace types and processes are not fully mature, and it will take some time for them to be truly widely used.
[0012] The Acheson graphitization furnace is the mainstream graphitization furnace type for negative electrode materials. It mainly loads the carbonaceous negative electrode material into a single-hole (1-hole crucible) crucible, then loads the crucible into the graphitization furnace and intersperses resistor materials as resistors. After the two sides and the upper cover are loaded with insulation materials, graphitization is completed by power supply. Although the technology is mature, the output is large, and the product homogeneity is good, the high energy consumption per ton is still a major problem currently faced. Summary of the invention
[0013] In view of the above-mentioned defects existing in the prior art, the purpose of the present invention is to provide a method for graphitizing a negative electrode material for a lithium ion battery and a negative electrode material for a lithium ion battery, the negative electrode material is pretreated, and the negative electrode material is made into a block material, and the block material is directly graphitized by bare firing in an Acheson graphitization furnace, which greatly reduces the energy consumption in the graphitization process and saves the cost of the crucible.
[0014] To achieve the above object, the present invention adopts the following technical solution:
[0015] A first aspect of the present invention provides a method for graphitizing a negative electrode material for a lithium ion battery, comprising the following steps:
[0016] S1, mixing the negative electrode powder with a binder and auxiliary additives to obtain a paste;
[0017] S2, the kneaded paste is cooled and then vibrated to obtain a block;
[0018] S3, after adding a graphite plate to the bottom of each piece of material, loading it into an Acheson furnace for graphitization treatment, to obtain a negative electrode material for a lithium-ion battery.
[0019] Preferably, in step S1:
[0020] The negative electrode powder is selected from a mixture of one or more of petroleum coke, asphalt coke, coal-based needle coke, oil-based needle coke and other coal cokes; and / or
[0021] The D50 particle size of the negative electrode powder is ≤20 μm
[0022] The binder uses a vitamin additive; and / or
[0023] The auxiliary additives include Fe3O4 and silicon powder.
[0024] Preferably, the vitamin additive is one or more of hydroxymethyl cellulose, hydroxyethyl cellulose and hydroxypropyl cellulose.
[0025] Preferably, in step S1:
[0026] The amount of the binder added is 5-25wt% of the negative electrode powder; and / or
[0027] The amount of the auxiliary additive added is 1 to 20 wt % of the negative electrode powder.
[0028] Preferably, in step S1, the kneading temperature is room temperature and the kneading time is 1.5 to 2 hours.
[0029] Preferably, in step S2, the cooling time is 1 to 2 hours.
[0030] Preferably, in the step S2, during the vibration molding process, the molding pressure is 5 to 10 tons and the molding time is 1 to 2 hours.
[0031] Preferably, in the step S3, during the graphitization treatment, the graphitization temperature is 2800-3000°C.
[0032] The second aspect of the present invention provides a lithium ion battery negative electrode material prepared by the graphitization method of the lithium ion battery negative electrode material according to the first aspect of the present invention.
[0033] Preferably, the specific surface area of the negative electrode material of the lithium ion battery is ≥1.45 g / m 2 , graphitization degree ≥ 96%; and / or
[0034] The first efficiency of the negative electrode material of the lithium ion battery is ≥95%, and the specific capacity is ≥350 mAh / g.
[0035] The graphitization method of the lithium ion battery negative electrode material and the lithium ion battery negative electrode material provided by the present invention have the following beneficial effects:
[0036] The present invention pre-treats the negative electrode powder, prepares the negative electrode powder into blocks by adding a binder and an auxiliary additive, and then graphitizes the blocks by direct bare firing in an Acheson graphitization furnace, thereby greatly reducing energy consumption in the graphitization process and saving the cost of the crucible. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Other features, objects and advantages of the present invention will become more apparent from the detailed description of non-limiting embodiments made with reference to the following drawings:
[0038] Figure 1 The figure is a schematic flow chart of the graphitization method of the negative electrode material of the lithium ion battery of the present invention. DETAILED DESCRIPTION
[0039] In order to better understand the above technical solution of the present invention, the technical solution of the present invention is further described below in conjunction with embodiments.
[0040] The core of the present invention lies in the processing and graphitization technology of block materials. The negative electrode material is pretreated and made into blocks. The blocks are directly graphitized by bare firing in an Acheson graphitization furnace, which greatly reduces the energy consumption in the graphitization process and saves the cost of crucibles.
[0041] Combination Figure 1 As shown, a graphitization method for a lithium ion battery negative electrode material of the present invention comprises the following steps:
[0042] S1, mixing the negative electrode powder with a binder and auxiliary additives to obtain a paste;
[0043] First, the negative electrode powder is mixed with a binder and auxiliary additives, wherein the negative electrode powder can be a mixture of one or more raw materials such as petroleum coke, asphalt coke, coal-based needle coke, oil-based needle coke and other coal cokes that can be used as negative electrode materials, and the D50 particle size of the negative electrode powder is ≤20μm; the binder is a vitamin additive, and the addition amount of the binder is 5-25wt% of the negative electrode powder; the vitamin additive is one or more of hydroxymethyl cellulose, hydroxyethyl cellulose, and hydroxypropyl cellulose; the auxiliary additives include Fe3O4 and silicon powder; the addition amount of the auxiliary additives is 1-20wt% of the negative electrode powder.
[0044] The negative electrode powder with good proportion is kneaded with the binder and auxiliary additives at room temperature for 1.5 to 2 hours to obtain a paste.
[0045] S2, the kneaded paste is cooled and then vibrated to obtain a block;
[0046] The kneaded paste is cooled to a certain plasticity (a small amount of granules are observed in the paste) for 1 to 2 hours; the paste is then vibrated and formed at a pressure of 5 to 10 tons for 1 to 2 hours to finally obtain a block material.
[0047] S3, after adding a graphite plate to the bottom of each piece of material, loading it into an Acheson furnace for graphitization treatment, to obtain a negative electrode material for a lithium-ion battery.
[0048] Specifically, in order to facilitate the subsequent material removal after graphitization, a graphite plate extending out of the bottom of each block is installed at the bottom of each block; then the block with the graphite plate installed is loaded into an Acheson furnace for graphitization treatment, wherein the graphitization treatment parameters are: the graphitization temperature is 2800-3000°C, and the block after graphitization treatment can be simply crushed to obtain a lithium-ion battery negative electrode material; the specific surface area of the lithium-ion battery negative electrode material is ≥1.45g / m 2 , graphitization degree ≥96%, first efficiency ≥95%, specific capacity ≥350mAh / g.
[0049] The energy consumption per ton in the above process of preparing the negative electrode material for lithium-ion batteries is ≤4100 kWh / ton.
[0050] The graphitization method of the negative electrode material for a lithium-ion battery of the present invention is further introduced below with reference to specific examples.
[0051] Example 1
[0052] A graphitization method for a negative electrode material of a lithium-ion battery in this embodiment, the specific process is as follows:
[0053] The negative electrode powder is made of petroleum coke and asphalt coke, the binder is hydroxymethyl cellulose among the cellulose additives, and the auxiliary additives are Fe3O4 and silicon powder.
[0054] A negative electrode powder with a D50 of 15 μm was used, 20% of cellulose and 15% of auxiliary additives were added for kneading, the kneading time was 2 hours, the kneading temperature was room temperature, a paste was obtained, the paste was cooled to a certain plasticity (a small amount of granules were observed in the paste), and then the paste was vibrated and formed, the molding pressure was 10 tons, the molding time was 1 hour, a graphite plate growing out of the bottom of the block was added to the bottom of the block obtained after molding, and then the block was loaded into a furnace for graphitization, wherein the graphitization temperature was 2900 ° C, and a lithium ion battery negative electrode material was obtained, the performance of which was 95.3% of the first efficiency, 357 mAh / g of specific capacity, and 1.56 g / m of specific surface area. 2 , the graphitization degree is 97.1%, and the energy consumption per ton is 4100kWh / ton.
[0055] Example 2
[0056] A graphitization method for a negative electrode material of a lithium-ion battery in this embodiment, the specific process is as follows:
[0057] The negative electrode powder is made of coal-based needle coke, the binder is hydroxyethyl cellulose among the cellulose additives, and the auxiliary additives are Fe3O4 and silicon powder.
[0058] A negative electrode powder with a D50 of 16 μm was used, 20% of cellulose and 10% of auxiliary additives were added for kneading, the kneading time was 1.5 hours, the kneading temperature was room temperature, and a paste was obtained. The paste was cooled to a certain plasticity (a small amount of granules were observed in the paste), and then the paste was vibrated and formed, the molding pressure was 5 tons, and the molding time was 1.5 hours. A graphite plate growing out of the bottom of the block was added to the bottom of the block obtained after molding, and then the block was loaded into a furnace for graphitization, wherein the graphitization temperature was 2800°C, and a lithium-ion battery negative electrode material was obtained, and its performance was 96.7% of the first efficiency, 356 mAh / g of specific capacity, and 1.45 g / m of specific surface area. 2 , graphitization degree is 96.8%, 3900kWh / ton.
[0059] Those skilled in the art should recognize that the above embodiments are only used to illustrate the present invention, and are not intended to limit the present invention. As long as they are within the spirit of the present invention, any changes or modifications to the above embodiments will fall within the scope of the claims of the present invention.
Claims
1. A method for graphitizing a negative electrode material for a lithium-ion battery, It is characterized in that The following steps are involved: S1, mixing the negative electrode powder with a binder and auxiliary additives to obtain a paste; S2, the kneaded paste is cooled and then vibrated to obtain a block; S3, after adding a graphite plate to the bottom of each piece of material, loading it into an Acheson furnace for graphitization treatment, to obtain a negative electrode material for a lithium-ion battery.
2. The graphitization method of the negative electrode material for lithium-ion batteries according to claim 1, It is characterized in that In step S1: The negative electrode powder is selected from a mixture of one or more of petroleum coke, asphalt coke, coal-based needle coke, oil-based needle coke and other coal cokes; and / or The D50 particle size of the negative electrode powder is ≤20 μm; and / or The binder uses a vitamin additive; and / or The auxiliary additives include Fe 3 O 4 and silica fume.
3. The graphitization method of the negative electrode material of a lithium ion battery according to claim 2, It is characterized in that The vitamin additive is one or more of hydroxymethyl cellulose, hydroxyethyl cellulose and hydroxypropyl cellulose.
4. The method for graphitizing a negative electrode material for a lithium ion battery according to claim 1, It is characterized in that In step S1: The amount of the binder added is 5-25wt% of the negative electrode powder; and / or The amount of the auxiliary additive added is 1 to 20 wt % of the negative electrode powder.
5. The method for graphitizing a negative electrode material for a lithium ion battery according to claim 1, It is characterized in that In the step S1, the kneading temperature is room temperature, and the kneading time is 1.5 to 2 hours.
6. The method for graphitizing a negative electrode material for a lithium ion battery according to claim 1, It is characterized in that In step S2, the cooling time is 1 to 2 hours.
7. The method for graphitizing a negative electrode material for a lithium ion battery according to claim 1, It is characterized in that In the step S2, during the vibration molding process, the molding pressure is 5 to 10 tons and the molding time is 1 to 2 hours.
8. The method for graphitizing a negative electrode material for a lithium ion battery according to claim 1, It is characterized in that In the step S3, during the graphitization process, the graphitization temperature is 2800-3000°C.
9. A negative electrode material for a lithium ion battery prepared by the graphitization method for a negative electrode material for a lithium ion battery according to any one of claims 1 to 8.
10. The lithium ion battery negative electrode material according to claim 9, Features: The specific surface area of the negative electrode material of the lithium ion battery is ≥1.45g / m 2 , graphitization degree ≥ 96%; and / or The first efficiency of the negative electrode material of the lithium ion battery is ≥95%, and the specific capacity is ≥350 mAh / g.
Citation Information
Patent Citations
Carbon material for non-aqueous secondary battery, anode using said carbon material, and non-aqueous secondary battery
CN103518279A
Preparation method of high-rate graphite anode material, anode material and lithium-ion battery
CN105633408A
Preparation method of special activated-carbon electrode block for capacitive deionizing equipment
CN106395814A
Lithium battery graphite anode material production process
CN108101042A
Method for recovering a lithium ion battery anode material
CN108879014A
